Effectiveness of hydrogen rich water on antioxidant status of subjects with potential metabolic syndrome-an open label pilot study - Nakao, Atsunori; Toyoda, Yoshiya; Sharma, Prachi; Evans, Malkanthi; Guthrie, Najla (Journal of clinical biochemistry and nutrition, 2010)
Metabolic syndrome is characterized by cardiometabolic risk factors that include obesity, insulin resistance, hypertension and dyslipidemia. Oxidative stress is known to play a major role in the pathogenesis of metabolic syndrome. The objective of this study was to examine the effectiveness of hydrogen rich water (1.5-2 L/day) in an open label, 8-week study on 20 subjects with potential metabolic syndrome. Hydrogen rich water was produced, by placing a metallic magnesium stick into drinking water (hydrogen concentration; 0.55-0.65 mM), by the following chemical reaction; Mg + 2H(2)O --> Mg (OH)(2) + H(2). The consumption of hydrogen rich water for 8 weeks resulted in a 39% increase (p<0.05) in antioxidant enzyme superoxide dismutase (SOD) and a 43% decrease (p<0.05) in thiobarbituric acid reactive substances (TBARS) in urine. Further, subjects demonstrated an 8% increase in high density lipoprotein (HDL)-cholesterol and a 13% decrease in total cholesterol/HDL-cholesterol from baseline to week 4. There was no change in fasting glucose levels during the 8 week study. In conclusion, drinking hydrogen rich water represents a potentially novel therapeutic and preventive strategy for metabolic syndrome. The portable magnesium stick was a safe, easy and effective method of delivering hydrogen rich water for daily consumption by participants in the study.